How have changes to out-of-hours primary care services since 2004 affected emergency department attendances at a UK District General Hospital? A longitudinal study. Issue 1 (22nd December 2009) - Thompson, C; Hayhurst, C; Boyle, A
Abstract : Background: The delivery of out-of-hours primary medical care in the United Kingdom has changed substantially since 2004, and there has been little examination of the effect that this has on secondary care. Aim: The authors aimed to quantify the change in patient type presenting to our emergency department. Methods: In this study, routinely collected coding data before, during and after the changes were analysed. Each September and October between 1999 and 2006 were included. Results: There was a steady increase in all attendances at our emergency department. The number and proportions of patients with non-traumatic conditions rose steadily throughout the study period. The number of patients presenting with traumatic conditions stayed the same. The number of patients presenting with non-traumatic conditions out-of-hours rose after the changes were implemented. Interpretation: The changes to the provision of out-of-hours primary care have been associated with an increase in patients with non-traumatic attendances presenting to our emergency department. This effect is most marked outside of office hours.